Room temperature yellow InGaAlP quantum dot laser. (May 2019) - Ledentsov, N.N.; Shchukin, V.A.; Shernyakov, Yu. M.; Kulagina, M.M.; Payusov, A.S.; Gordeev, N. Yu.; Maximov, M.V.; Zhukov, A.E.; Karachinsky, L. Ya.; Denneulin, T.; Cherkashin, N.
Highlights: Visible semiconductor lasers. Tensile strained barriers. High–index substrates. Quantum dot active medium. High resolution dark–field electron holography. Abstract: We report simulation of the conduction band alignment in tensile–strained GaP–enriched barrier structures and experimental results on injection lasing in the green–orange spectral range (558–605 nm) in (Alx Ga1–x )0.5 In0.5 P–GaAs diodes containing such barriers. The wafers were grown by metal–organic vapor phase epitaxy side–by–side on (8 1 1)A, (2 1 1)A and (3 2 2)A GaAs substrates, which surface orientations were strongly tilted towards the [1 1 1]A direction with respect to the (1 0 0) plane. Four sheets of GaP–rich quantum barrier insertions were applied to suppress the leakage of non–equilibrium electrons from the gain medium. Two types of the gain medium were applied. In one case 4–fold stacked tensile–strained (In, Ga)P insertions were used. Experimental data shows that self–organized vertically–correlated quantum dots (QDs) are formed on (2 1 1)A– and (3 2 2)A–oriented substrates, while corrugated quantum wires are formed on the (8 1 1)A surface. In the other case a short–period superlattice (SPSL) composed of 16–fold stacked quasi–lattice–matched 1.4 nm–thick In0.5 Ga0.5 P layers separated by 4 nm–thick (Al0.6 Ga0.4 )0.5 In0.5 P layers was applied. Laser diodes with 4–fold stacked QDs having a threshold current densities of ∼7–10 kA/cm 2 at room temperature were realized for both (2 1 1)A and (3 2 2)A surface orientations at cavity lengths of ∼1 mm. Emission wavelength at room temperature was ∼599–603 nm. Threshold current density for the stimulated emission was as low as ∼1 kA/cm 2 . For (8 1 1)A–grown structures no room temperature lasing was observed. SPSL structures demonstrated lasing only at low temperatures <200 K. The shortest wavelength (558 nm, 90 K) in combination with the highest operation temperature (150 K) was realized for (3 2 2)A–oriented substrates in agreement with theoretical predictions.